SHORT-TIMESCALE VARIATION OF PHYTOPLANKTON ABUNDANCE AND DIVERSITY AT REDANG ISLAND - Joon, Hai Lim; Choon, Weng Lee (Malaysian Journal of Science, 2015)
A short-timescale sampling of phytoplankton abundance and diversity was carried out at Redang Island waters, South China Sea. Physico-chemical variables measured at four intervals over a day were relatively stable (temperature = 29 ± 0.6°C ; salinity = 27 ± 2 ppt, pH = 7.8 ± 0.1; total alkalinity = 2025 ± 33 µeq l–1) whereas inorganic nutrient concentrations (NH4 = 1.36 ± 0.51 µM; NO2 = 0.06 ± 0.03 µM; PO4 = 0.08 ± 0.03 µM; and SiO4 = 9.98 ± 0.54 µM) were low and reflected oligotrophic conditions. The oligotrophic nature of Redang Island waters supported relatively lower biomass i.e. bacterial abundance = 6.6 ± 0.5 × 105 cell ml–1; picoplankton abundance = 9.3 ± 0.8 × 104 cell ml–1; phytoplankton abundance = 4.8 ± 2.2 × 103 cell ml–1 and zooplankton abundance = 1.18 ± 0.57 × 103 cell l–1. Phytoplankton community was made up of ten genera (Asteramphalus sp., Bacteriastrum sp., Chaetoceros sp., Cosinodiscus sp., Diploneis sp., Hemialus sp., Leptocylindricus sp., Navicula sp., Nitzschia sp., and Rhizosolenia sp.), and significantly different from near-shore waters. Redang Island waters exhibited a simpler phytoplankton community which is probably more susceptible to climate change. Keywords: coral reef, Redang Island, phytoplankton abundance, phytoplankton diversity, Sunda Shelf